2017
DOI: 10.1093/mnras/stx478
|View full text |Cite
|
Sign up to set email alerts
|

Neutrino-heated winds from millisecond protomagnetars as sources of the weak r-process

Abstract: We explore heavy element nucleosynthesis in neutrino-driven winds from rapidly-rotating, strongly magnetized proto-neutron stars ("millisecond proto-magnetars") for which the magnetic dipole is aligned with the rotation axis, and the field is assumed to be a static force-free configuration. We process the proto-magnetar wind trajectories calculated by Vlasov et al. (2014) through the r-process nuclear reaction network SkyNet using contemporary models for the evolution of the wind electron fraction during the p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 110 publications
2
47
0
Order By: Relevance
“…The 1D solutions of Metzger et al (2008c) were calculated along flow lines which emerge along the equatorial plane, near the last closed field line. Because these lowlatitude lines cover a large solid angle and carry most of the total mass flux of the wind, the results are similar to the total mass-loss rate and mass-averaged value of the outflow Y e integrated across the full open magnetosphere (Vlasov et al 2014(Vlasov et al , 2017. Nevertheless, the wind velocity and composition do show moderate variation with polar latitude θ of the outflow launching point; for instance, Vlasov et al (2014) found that for P ≈ 1 ms and L ν ≈ 2 × 10 52 ergs s −1 , Y e varied from ≈ 0.40 to ≈ 0.32 as θ increased from 0.35 to ≈ 0.5 (flow lines which carry ≈ 20% and ≈ 80% of the total mass loss, respectively).…”
Section: Magnetized Neutrino-heated Windsupporting
confidence: 52%
“…The 1D solutions of Metzger et al (2008c) were calculated along flow lines which emerge along the equatorial plane, near the last closed field line. Because these lowlatitude lines cover a large solid angle and carry most of the total mass flux of the wind, the results are similar to the total mass-loss rate and mass-averaged value of the outflow Y e integrated across the full open magnetosphere (Vlasov et al 2014(Vlasov et al , 2017. Nevertheless, the wind velocity and composition do show moderate variation with polar latitude θ of the outflow launching point; for instance, Vlasov et al (2014) found that for P ≈ 1 ms and L ν ≈ 2 × 10 52 ergs s −1 , Y e varied from ≈ 0.40 to ≈ 0.32 as θ increased from 0.35 to ≈ 0.5 (flow lines which carry ≈ 20% and ≈ 80% of the total mass loss, respectively).…”
Section: Magnetized Neutrino-heated Windsupporting
confidence: 52%
“…They suggest that the wind develops only in the lowest-mass cases. (ii) The above mentioned investigations for magneto-rotational supernovae predict dynamical ejecta of the order 0.01-0.1 M , while the wind ejecta of Vlasov et al (2017) for fast rotating magnetized protoneutron stars (which should follow such dynamical ejecta) are of the order 10 −4 to 10 −3 M . Here one might need to include both such ejecta (the dynamical as well as the wind ejecta), which we will discuss when considering case (c).…”
Section: Identifying the Suggested R-process Sources / Event Categori...mentioning
confidence: 93%
“…In the literature one can find further suggestions for weak rprocess sites, i.e. predictions from neutrino winds of magnetized neutron stars (Vlasov et al 2017) and from neutrino winds of regular CCSNe following the explosions (e.g. Wanajo 2013).…”
Section: Identifying the Suggested R-process Sources / Event Categori...mentioning
confidence: 95%
See 1 more Smart Citation
“…1). SkyNet has been used for r-process nucleosynthesis calculations in different scenarios by various authors: [3][4][5][6][7][8][9].…”
Section: Astrophysical Simulations Of Nucleosynthetic Environmentsmentioning
confidence: 99%

FRIB and the GW170817 Kilonova

Aprahamian,
Surman,
Frebel
et al. 2018
Preprint
Self Cite